Implementasi Pembelajaran Pendidikan Agama Kristen Menggunakan Pendekatan Model Quantum Learning - Marthen Mau (APOSTOLOS, 2021)
Christian religious education teachers need to pay attention to changes in the character, character, attitude and character of students. The formation of character, character, attitude, and character of students is needed through Christian religious education learning. One of the important learning models that can be used in Christian religious education learning is the quantum learning approach. The purpose of this study is to implement a comfortable and satisfying teaching and learning process for students in the classroom or learning environment. This study the authors used a qualitative method with a literature approach. The result of this study is that the quantum learning approach is very good for use in the PAK learning process because students will feel proud, happy, happy, comfortable, and have a sense of satisfaction in a learning environment, especially in formal educational institutions. The PAK learning process uses a quantum learning approach, so it is beneficial for students. Thus, when carrying out the learning process in the classroom can form study groups of 2-3 student members, the PAK learning will run well and smoothly, so that students get satisfying learning benefits even though it is quite challenging for themselves.